Most marketed herbal medicines from 2020 to 2021 in a drugstore located in Manaus - AM - Brazil (Research, Society and Development, 2021)
Objectives: This article has as its main objective to analyze the phytotherapy drugs that were most sold between September 2020 and September 2021 in a drugstore in the city. Methods: To list the main phytotherapeutic drugs sold between September 2020 and September 2021; punctuate the effects of irrational use of herbal medicine based on Mikania glomerata (popularly known as guaco); this work is exploratory research carried out, using documentary and bibliographic research. Results: 6620 herbal medicines were sold between September/2020 and September/2021, out of this total, 1820 herbal medicines were sold and the most sold was the herbal medicine with the plant species Mikania glomerata, with 384 units sold. Conclusion: the amount of demand related to Guaco syrup is related to the efficiency of this phytotherapy linked to the alternative of medicines during the SARS-CoV-2 pandemic, which causes the individual to present flu symptoms and seek these medications.